German Government Official Methods Board Points the Way Forward: Launch of a New Working Group for Mass Spectrometry for Protein Analysis to Detect Food Fraud and Food Allergens. (3rd December 2019) - Stoyke, Manfred; Becker, René; Brockmeyer, Jens; Jira, Wolfgang; Popping, Bert; Uhlig, Steffen; Wittke, Stefan
Abstract: The detection of food fraud and undeclared food allergens is one of the major challenges for competent authorities. Because adulterations are continuously adapted to the methods used to uncover them, the accomplishment of this task has become increasingly difficult over time. In recent years, various new promising methods for the detection of multiple food adulterants and multiple food allergens have been developed. Some of them utilize LC–MS to identify specific marker peptides. However, these methods have yet to be validated and standardized. For this reason, the German officials have established a working group with the objective of validating methods through multilaboratory validation studies. The experts of the working group also aim for the first time to standardize validated methods and to develop general validation criteria. This manuscript will highlight the current work of the group. For this purpose, an overview is given on the principles and applications of the new mass spectrometric methods. Moreover, requirements and the present work of other institutions regarding method validation are described.